Video-Assisted Anal Fistula Treatment: Pros and Cons of This Minimally Invasive Method for Treatment of Perianal Fistulas - Michal Romaniszyn; Piotr Walega (Gastroenterology Research and Practice)
Purpose. The purpose of this paper is to present results of a single-center, nonrandomized, prospective study of the video-assisted anal fistula treatment (VAAFT). Methods. 68 consecutive patients with perianal fistulas were operated on using the VAAFT technique. 30 of the patients had simple fistulas, and 38 had complex fistulas. The mean follow-up time was 31 months. Results. The overall healing rate was 54.41% (37 of the 68 patients healed with no recurrence during the follow-up period). The results varied depending on the type of fistula. The success rate for the group with simple fistulas was 73.3%, whereas it was only 39.47% for the group with complex fistulas. Female patients achieved higher healing rates for both simple (81.82% versus 68.42%) and complex fistulas (77.78% versus 27.59%). There were no major complications. Conclusions. The results of VAAFT vary greatly depending on the type of fistula. The procedure has some drawbacks due to the rigid construction of the fistuloscope and the diameter of the shaft. The electrocautery of the fistula tract from the inside can be insufficient to close wide tracts. However, low risk of complications permits repetition of the treatment until success is achieved. Careful selection of patients is advised.